The effect of using Appleton’s model on fifth- primary grade pupils’ scores and trends toward social textbooks. (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to identify the effect of using the Appleton’s model on fifth- primary grade pupils’ scores in social textbooks. To achieve the objectives, the researcher used the experimental approach with a partial control design containing two groups; the experimental and the control group. The researcher randomly selected a sample of (60) pupils distributed equally to the two groups. The research tools are the post test scores which consisted of (40) items and the measurement of the trend towards the material which consisted of (30) items. Validity and reliability were confirmed by using the appropriate statistical means. After applying the experiment to the research sample, it was clear that the experimental group that was taught using the Appleton’s model exceeded the control group in the two variables; scores and trend toward the material. In light of the results, the researcher presented a number of recommendations and suggestions, including using the Appleton’s model in teaching and holding courses to identify the model and its steps. The researcher suggested using the Appleton’s model   In different stages and subjects.